2022
DOI: 10.3389/fimmu.2022.871200
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Pro-Resolving Mediators Reduce Scarring After Cleft Lip Repair

Abstract: ObjectiveResidual scarring after cleft lip repair surgery remains a challenge for both surgeons and patients and novel therapeutics are critically needed. The objective of this preclinical experimental study was to evaluate the impact of the methyl-ester of pro-resolving lipid mediator lipoxin A4 (LXA4-ME) on scarring in a novel rabbit model of cleft lip repair.MethodsA defect of the lip was surgically created and repaired in eight six-week old New Zealand white rabbits to simulate human cleft lip scars. Rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…25 Preclinical studies have shown LXA 4 -ME limits scarring after cleft lip repair in rabbits, suggesting new therapeutic opportunities in the prevention and management of pathologic scarring in. 55 The present study hypothesized that certain scar subsites may also be associated with treatment type and response to treatment. Alo et al found that different scar locations correspond with certain morphological patterns, postulating that location and morphology may influence treatment.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…25 Preclinical studies have shown LXA 4 -ME limits scarring after cleft lip repair in rabbits, suggesting new therapeutic opportunities in the prevention and management of pathologic scarring in. 55 The present study hypothesized that certain scar subsites may also be associated with treatment type and response to treatment. Alo et al found that different scar locations correspond with certain morphological patterns, postulating that location and morphology may influence treatment.…”
Section: Discussionmentioning
confidence: 88%
“…Emerging evidence suggests that specialized pro‐resolving mediators of inflammation such as methyl‐ester of pro‐resolving lipid mediator lipoxin A 4 (LXA 4 ‐ME) prevent chronic inflammation, thus accelerating wound healing after cleft lip repair and facilitating healthy tissue remodeling 25 . Preclinical studies have shown LXA 4 ‐ME limits scarring after cleft lip repair in rabbits, suggesting new therapeutic opportunities in the prevention and management of pathologic scarring in 55 …”
Section: Discussionmentioning
confidence: 99%
“…77 Decreased inflammation resulting from resolvin treatment appears to alter scar formation as well, improving collagen alignment and visual scar assessment in a model of cleft lip palate surgery. 78 Wide range of actions of pro-resolving mediators in promoting tissue regeneration, controlling infections, and facilitating the resolution of inflammation has been recently reviewed. 79 It remains to be seen if VNS can upregulate pro-resolving mediators in skin wounds and contribute to wound repair.…”
Section: How Vns Can Modulate Cutaneous Inflammationmentioning
confidence: 99%
“…A wound dressing that contains abundant SPMs (LIPINOVA®, Solutex, Madrid, Spain) reduced pro‐inflammatory macrophages, while increasing anti‐inflammatory Mφ2 polarisation and promoting wound closure in db/db mice 77 . Decreased inflammation resulting from resolvin treatment appears to alter scar formation as well, improving collagen alignment and visual scar assessment in a model of cleft lip palate surgery 78 . Wide range of actions of pro‐resolving mediators in promoting tissue regeneration, controlling infections, and facilitating the resolution of inflammation has been recently reviewed 79 .…”
Section: Pre‐clinical Studiesmentioning
confidence: 99%